2022
DOI: 10.1177/10634266221120532
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Child Mental Health Intervention in Child Welfare Services: Stakeholder Perspectives on Feasibility

Abstract: This pilot study integrated quantitative and qualitative data to examine the feasibility of implementing a modified version of a multiple family group behavioral parent training intervention (The 4Rs and 2Ss for Strengthening Families Program [4Rs and 2Ss]) in child welfare (CW) placement prevention services from the perspectives of participating caregivers ( n = 12) and CW staff ( n = 12; i.e., 6 caseworkers, 4 supervisors, and 2 administrators). Quantitative surveys were administered to caregivers and CW sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…A previous publication describes the modification process. 18 Between 2015 and 2017, the intervention was delivered in the CW agency to three cohorts of families, with the University providing critical support -both financial (for transportation, childcare, food) and research (fidelity monitoring and supervision).…”
Section: Purpose and Background Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A previous publication describes the modification process. 18 Between 2015 and 2017, the intervention was delivered in the CW agency to three cohorts of families, with the University providing critical support -both financial (for transportation, childcare, food) and research (fidelity monitoring and supervision).…”
Section: Purpose and Background Of This Studymentioning
confidence: 99%
“…By comparison, the attendance rates for the modified 4 Rs and 2 Ss Strengthening Families Program were lower than those reported in this study. 18 This may be attributed to a key adaptation the agency made: moving the intervention beyond agency walls into community settings (library, community center, online). Palinkas and colleagues 37 found that providing incentives for participation was an indicator to sustainment of a service.…”
Section: Purposeful Adaptationsmentioning
confidence: 99%